Principles of Rational Nutrition for Managing Constipation - Yu. O. Shulpekova; D. A. Sheptulin; N. V. Shulpekova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. The aim of this work was to investigate the problem of constipation associated with a deficiency in dietary fibre and to develop principles for the nutritional management of this condition.  Main findings. In countries characterized by the Western-style diet, only about 10% of people consume an optimal amount of fibre daily. As a result, primary normal-transit constipation is a common problem. A special role in maintaining the function of the colon belongs to carbohydrates. Keeping a food diary helps to choose an optimal type of nutrition for a patient and reduce the likelihood of flatulence. Food fibres (oligosaccharides and polysaccharides) play an especially important role. Viscous fibres are most capable of swelling, thus exhibiting metabolic effects at the level of the small intestine. Non-viscous and insoluble fibres increase the volume of feces, stimulate peristalsis and exert a prebiotic effect. A low content of fibre in the diet is a factor provoking intestinal dysbiosis followed by a decrease in  Bacteroides and Ruminococcus populations. Flavonoids also play an important role in the regulation of intestinal peristalsis and secretion. Under constipation of functional origin, the microbiota contains a significantly reduced amount of Bifidobacterium and Bacteroides. Changes in the composition of microflora correlate with psychopathological symptoms. Strains capable of exhibiting a therapeutic effect in constipation include Escherichia coli Nissle 1917, a probiotic mixture of VSL#3, Florasan-D combined bacterium, DN-173 010 Bifidobacterium lactis (B. lactis), HN019 Bifidobacterium lactis and Lactobacillus rhamnosus GG. For the prevention and management of constipation, functional food products enriched with oligo-, polysaccharides and probiotics are developed. Thus, various products of the Activia brand contain DN-173 010 Bifidobacterium lactis (ActiRegularis) at a concentration of at least 108 CFU / g. The consumption of fermented milk products with DN-173-010 Bifidobacterium lactis contributes to the elimination of subclinical discomfort in the abdomen in practically healthy people, reduces the time of colon transit and helps to normalise the frequency of defecation.Conclusion. In most cases, the first stage in managing constipation is the normalisation of the diet by means of adding dietary fibre and probiotics into the composition of functional foods or medical preparations.